Pelatihan pembuatan kerajinan tangan dari benang macrame pada anak-anak di Desa Wisata Sangurejo Kecamatan Turi Kabupaten Sleman - Putri, Wanda Adelya; Rahmawati, Yeni (CV. Kurnia Grup, 2024)
Kuliah Kerja Nyata (KKN) is a form of real student service to the community. KKN activities are expected to create a tough, superior, noble personality, and can be an extraordinary person when they are involved in the community, and have a leadership spirit. This KKN is located in Sangurejo Padukuhan, Wonokerto Sub-district, Kapanewon Turi, Sleman Regency, Yogyakarta Special Region. Sangurejo Tourism Village is one of the tourist villages located in Sangurejo Sub-Village, Wonokerto Village, Kapanewon Turi, Sleman Regency. The author's programme is Training On The Making Of Hand Craft From Macrame Yarn For Students Sangurejo Villages. The purpose of programme training is to increase creativity and create young entrepreneurship.